Reviewer recognition. Issue 8 (December 2018) - Unknown
We would like to thank all those listed below for taking the time to review forGene Therapy in 2017—your generosity is much appreciated and we hope your association with the journal continues in the future. Editor-in-Chief: Rafael Yáñez-Muñoz We will be awarding the top reviewers with a 1-year gratis subscription toGene Therapy andNature as a special thank you for their time. Nevertheless the support from all of you is vital to the journal and we wish to sincerely thank you all too: